1996
DOI: 10.1536/ihj.37.917
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Passive Exposure to Tobacco, Socioeconomic Status and a Family History of Essential Hypertension on Lipid Profiles in Children.

Abstract: SUMMARYThere is abundant evidence that the atherosclerotic process begins in childhood. Dyslipidemia is a major risk factor for atherosclerosis in adults and children. In the present study, we measured serum lipoprotein concentrations in 194 healthy children aged between 4 to 14 years. Children were grouped according to the socioeconomic status of the families, family history of essential hypertension and passive tobacco exposure. The values of total cholesterol, low density lipoprotein cholesterol and the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…It was also found that PS is associated with deteriorated blood lipids profiles in children, particularly lower high-density lipoprotein which has been a consistent finding in most studies [1721]. A randomized controlled trial (RCT) also revealed that in passive smokers the rate of factors associated with the development of CVD, such as body weight, cholesterol, and triglycerides, was higher than that in non-PS smokers [22].…”
Section: Resultsmentioning
confidence: 72%
“…It was also found that PS is associated with deteriorated blood lipids profiles in children, particularly lower high-density lipoprotein which has been a consistent finding in most studies [1721]. A randomized controlled trial (RCT) also revealed that in passive smokers the rate of factors associated with the development of CVD, such as body weight, cholesterol, and triglycerides, was higher than that in non-PS smokers [22].…”
Section: Resultsmentioning
confidence: 72%
“…SES also affects health behaviors. Lower SES is associated with increased rates of cigarette smoking, greater exposure to tobacco smoke, and more sedentary lifestyles (see Conrad, Flay, & Hill, 1992, for a review of smoking, and Stephens, Jacobs, & White, 1985, for a review of physical activity; Coombs, Fawzy, & Gerber, 1986; Iscan, Uyanik, Vurgun, Ece, & Yigitoglu, 1996; Pamuk et al, 1998).…”
Section: Nature Of Ses Relationship In Childhood and Adolescencementioning
confidence: 99%
“…We used the unpaired Student'\ t-test analysis to assess differences between mean values of lipids and lipoproteins between groups, adjusted 13) age. sex, BMI and other factors.…”
Section: Statistical Analysesmentioning
confidence: 99%